2022
DOI: 10.3389/fvets.2022.957306
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of lumpy skin disease outbreaks in dairy farms in northeastern Thailand

Abstract: In 2021–2022, there were numerous outbreaks of lumpy skin disease (LSD) affecting cattle farms across Thailand. This circumstance was the country's first encounter with an LSD outbreak. Thus, a better understanding of LSD epidemiology is necessary. The aim of this study was to determine the spatio-temporal patterns of the LSD outbreaks in dairy farming areas. Data from LSD outbreak investigations collected from dairy farms in Khon Kean province, northeastern Thailand, were analyzed using spatio-temporal models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Regarding the spread modalities, the studies included in this literature review [ 54 , 58 , 60 , 69 ] reported that short-distance spread (i.e., between herds) was most likely attributed to a dispersal by arthropod vectors, whereas long-distance spread (i.e., transboundary, introduction into new geographical areas) was related to livestock movements. Both short- and long-distance spreads are associated with climatic conditions, especially a high temperatures and rainfalls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the spread modalities, the studies included in this literature review [ 54 , 58 , 60 , 69 ] reported that short-distance spread (i.e., between herds) was most likely attributed to a dispersal by arthropod vectors, whereas long-distance spread (i.e., transboundary, introduction into new geographical areas) was related to livestock movements. Both short- and long-distance spreads are associated with climatic conditions, especially a high temperatures and rainfalls.…”
Section: Resultsmentioning
confidence: 99%
“…The authors inferred that transmission occurred over <5 km distances, which can be attributed to vectors, but with an appreciable probability of transmission over longer distances, that can be related to livestock movements [ 60 ]. Spatio-temporal analysis of LSD outbreaks that affected dairy farms in north-eastern Thailand discovered that these outbreaks occurred in numerous dairy farms over a short period of time, and that several affected farms were concentrated in the area [ 58 ]. Based on these findings and on the fact that cattle movements between dairy farms are few, the spread was attributable to vectors.…”
Section: Resultsmentioning
confidence: 99%
“…This finding indicates that Thailand had the highest number of LSD outbreak reports compared to other countries in Asia in 2021. Because it was the first time Thailand faced this threat, LSD outbreaks were found in cattle herds across the country, causing serious economic loss to the cattle industry [ 25 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then it was spread into Yi li, Xinjiang Province, China in 2019. In the following 2 years, the disease spread to southern and eastern parts of China and the countries in South Asia, including Nepal, Bhutan, Vietnam, Thailand and Myanmar ( Pseudo-urticaria, 1931 ; Mulatu and Feyisa, 2018 ; Arjkumpa et al, 2021 ; Punyapornwithaya et al, 2022 ). By 2022, the disease had spread east and north to Mongolia and Eastern Siberia ( Figure 2 ).…”
Section: Epidemiologymentioning
confidence: 99%